2014
DOI: 10.1371/journal.pone.0092627
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Combined with Endoplasmic Reticulum Stress Induces Cell Death via the PI3K/Akt/mTOR Pathway in B16F10 Melanoma Cells

Abstract: This study investigated B16F10 melanoma cell death induced by melatonin combined with endoplasmic reticulum (ER) stress through the PI3K/Akt/mTOR pathway. Cell viability was significantly decreased after treatment with melatonin combined with ER stress from thapsigargin or tunicamycin compared to no treatment or treatment with melatonin only. Combined melatonin and ER stress also significantly reduced expression of p85β, p-Akt (Ser473, Thr308), and p-mTOR (Ser2448, Ser2481) compared to treatment with melatonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 53 publications
(41 reference statements)
5
51
1
1
Order By: Relevance
“…ERS is well-characterized in human LC [44, 45]. Recent evidence has suggested that ERS can initiate internal pathways that may induce cellular death [27]. The central objective of the ERS response is to limit disturbance and ultimately recover ER balance; however, in terms of intense or sustained ERS, these pathways will activate programmed cell apoptosis [46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ERS is well-characterized in human LC [44, 45]. Recent evidence has suggested that ERS can initiate internal pathways that may induce cellular death [27]. The central objective of the ERS response is to limit disturbance and ultimately recover ER balance; however, in terms of intense or sustained ERS, these pathways will activate programmed cell apoptosis [46].…”
Section: Discussionmentioning
confidence: 99%
“…ERS shares a correlation with the PI3K/Akt/mTOR signaling pathway. Our experimental data revealed that increases in ERS are followed by decreases in PI3K/AKT/mTOR signaling, as well as reductions in chemoresistance; when the PI3K/AKT/mTOR signaling pathway is blocked, autophagy and apoptosis factors are increased, chemotherapy resistance is weakened, and the tumor shrinks [27, 59], which has an important function in autophagy and apoptosis regulation [2, 60, 61]. It has been reported that blocking the PI3K/AKT/mTOR cascade promotes autophagy [62] that inhibiting PI3K/Akt/mTOR signaling promotes cell apoptosis in LC [28], which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanoma is a malignant tumor that arises from melanocytes, which produce black or brown melanin pigment in skin, bowel, and eyes, but over 90 % of all melanomas are cutaneous [40][41][42][43]. Despite significant progress in melanoma research over the years, there are no effective therapies for advanced melanoma at present [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Cellcycle study on osteocarcinoma MG-63 cell lines showed that MLT treatment arrests cells in G1 and G2/M phase of the cell cycle by the down-regulation of cyclin D1, CDK4, cyclin B and CDK1 (Liu et al, 2013). Similarly, MLT down-regulates the PI3K/AKT/mTOR (mammalian target of rapamycin) signalling pathway in B16F10 melanoma, which has been known for the proteosomal degradation of p27 (Kim et al, 2014). Furthermore, the flow- …”
Section: Induction Of Apoptosis and Cell-cycle Arrestmentioning
confidence: 99%